Review of Control Techniques for Wind Energy Systems - Hooman Ghaffarzadeh; Ali Mehrizi-Sani (Energies, 2020)
In recent years, penetration of renewable energy resources into the power grid has increased significantly. Wind, as a renewable, clean, and abundantly available source of energy, has an important share in the energy mix. However, increasing the penetration of wind power in the power grid can adversely affect the power quality and introduce new operational challenges. This paper discusses issues related to the integration of wind farms in the power system, such as maximum power point tracking, fault ride-through capabilities, interarea and subsynchronous oscillations, and voltage flicker, and provides a review of the existing control strategies to address these issues in Types I, II, III, and IV wind turbines. This paper also identifies challenges and opportunities ahead.